ANALISIS LOGOTERAPI TERHADAP PENGOBATAN KORBAN NAPZA DI YAYASAN MITRA ALAM SURAKARTA - Siti Fathonah; Indah Permatasari (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
One of treatment methods which begins to be developed to response various cases of drugs addiction is logotherapy. This research aims to investigate the practices of logotherapy in the rehabilitation program which was carried out for the victims of drug abuse in Institusi Penerima Wajib Lapor (IPWL) which belongs to Yayasan Mitra Alam Surakarta. This research is a field-research with phenomenological qualitative methodology. Data were garnered through interviews, observations, and documents. Data analysis was done by employing data analysis technique proposed by Moustakas. The results indicate that there are four concepts of logotherapy which exist in Yayasan Mitra Alam Surakarta. First, the therapists take distance between symptomps by detoxification. Second, the therapists modifies the attitude of the patients by giving rules and schedule of activities which applies reward and punishment system. Third, the therapists reduce the symptoms by employing dereflection and medical ministry techniques. Fourth, the therapists directs the patients’ orientation about the meaning of life by giving skills tailored to their interests and talents. This research concludes that the practices of logotherapy applied in Yayasan Mitra Alam Surakarta does not have identical similarity with logotherapy applied by pure logotherapy practitioners.